Direct Electrodeposition of Graphene‐Gold Nanocomposite Films for Ultrasensitive Voltammetric Determination of Mercury(II). Issue 1 (25th September 2013) - Ding, Liang; Liu, Yuping; Zhai, Jianping; Bond, Alan M.; Zhang, Jie
Abstract Graphene‐gold nanocomposite (rGO‐Au) modified glassy carbon electrodes (GCE) have been fabricated by a one‐step electrodeposition method. The nanocomposites were characterized by scanning electron microscopy, energy dispersive X‐ray spectroscopy, Raman spectra as well as electrochemical methods, and were utilized for mercury(II) detection via anodic stripping voltammetry. The peak stripping current was linearly dependent on the concentration of Hg(II) over the range of 1.0 to 150.0 nM and high selectivity and sensitivity (limit of detection 0.6 nM) and excellent stability/reusability were achieved. The applicability to environmental samples was successfully demonstrated by the direct determination of Hg(II) in tap water samples with minimal sample pretreatment.